Defining quality metrics and improving safety and outcome in allergy care. Issue 4 (21st January 2014) - Lee, Stella; Stachler, Robert J.; Ferguson, Berrylin J.
<x xml:space="preserve">Abstract</x> Background The delivery of allergy immunotherapy in the otolaryngology office is variable and lacks standardization. Quality metrics encompasses the measurement of factors associated with good patient‐centered care. These factors have yet to be defined in the delivery of allergy immunotherapy. We developed and applied quality metrics to 6 allergy practices affiliated with an academic otolaryngic allergy center. Methods This work was conducted at a tertiary academic center providing care to over 1500 patients. We evaluated methods and variability between 6 sites. Tracking of errors and anaphylaxis was initiated across all sites. A nationwide survey of academic and private allergists was used to collect data on current practice and use of quality metrics. Results The most common types of errors recorded were patient identification errors (n = 4), followed by vial mixing errors (n = 3), and dosing errors (n = 2). There were 7 episodes of anaphylaxis of which 2 were secondary to dosing errors for a rate of 0.01% or 1 in every 10, 000 injection visits/year. Site visits showed that 86% of key safety measures were followed. Analysis of nationwide survey responses revealed that quality metrics are still not well defined by either medical or otolaryngic allergy practices. Academic practices were statistically more likely to use quality metrics (p = 0.021) and perform systems reviews and audits in comparison to private practices (p = 0.005). Conclusion Quality metrics in allergy delivery can help improve safety and quality care. These metrics need to be further defined by otolaryngic allergists in the changing health care environment.